(untitled) (Latakia University Journal -Medical Sciences Series, 2016)
شملت الدراسة عينات من حليب الرضع للعمر الأول والثاني لخمس شركات A, B, C, D, E. تم اتباع طريقةAssociation of Analytical Communities (AOAC, 2006)في تحديد حمض الأسكوربيك من خلال معايرته حجمياً باستخدام 6,2-دي كلوروفينول إندوفينول2,6- Dichlorophenolindophenol (DCPIP). كان محتوى حمض الأسكوربيك في حليب الرضع للشركتين D, Cقريباً من المصرح عنه في بطاقة البيان، أما حليب الرضع للشركات الباقية كان منخفضاً ووصل هذا الانخفاض إلى 34%في حليب الرضع للشركة E، وبقي المحتوى من حمض الأسكوربيك ثابتاً في عينات الحليب الجاف المحفوظة لمدة أسبوع بعد الفتح سواء في البراد أو في درجة حرارة الغرفة.انخفض المحتوى من حمض الاسكوربيك في عينات حليب عند تحضيرها باستخدام ماء حرارته40°CأوC100 مقارنة مع تلك المحضرة بماء الصنبور وازداد الانخفاض مع حفظ هذه العينات لمدة ساعتين بعد التحضير. Vitamin C concentration was studied in samples of infant formula from 5 companies (referenced A-E) using the 2,6-Dichlorophenolindophenol titration (AOAC, 2006) method. Results revealed that ascorbic acid content in formulas D and C was the closest to its recommended daily intake (RDI) and to the concentrations which are mentioned on the label of the samples. Storage conditions at room temperature or in the refrigerator did not affect ascorbic acid levels. In comparison to vitamin C concentrations in milk dissolved in tap water, its levels decreased when water was warm (40°C) or hot (100°C), and its concentrations further declined in dissolved form kept for two hours after preparation.